11β Hydroxysteroid dehydrogenase type 1 is expressed and is biologically active in human skeletal muscle - Jang, Christina; Obeyesekere, Varuni R.; Dilley, Rodney J.; Alford, Frank P.; Inder, Warrick J. (Clinical endocrinology (Oxford), 2006)
Summary Objective  No data exist regarding the distribution and oxoreductase enzyme activity of 11β hydroxysteroid dehydrogenase type 1 (11β HSD‐1) in fresh human skeletal muscle. We aimed to investigate the mRNA and protein expression of 11β HSD‐1 in fresh skeletal muscle, confirm its biological activity and determine its relationship with hexose‐6‐phosphate dehydrogenase (H6PDH). We also examined the muscle fibre localization of 11β HSD‐1. Design  Eleven non‐diabetic community volunteers underwent muscle biopsy of vastus lateralis. Measurements  (i) 11β HSD‐1 and H6PDH mRNA expression by quantitative reverse transcription polymerase chain reaction (RT‐PCR); (ii) protein localization and fibre type specificity by immunohistochemistry; and (iii) enzyme oxoreductase activity by percentage conversion of 3H cortisone to cortisol. Results  11β HSD‐1 mRNA was expressed at low levels compared to human liver. Mean ΔCT of skeletal muscle in 11 subjects was 19·57 (range 18·40–20·79) compared to ΔCT of 12·75 in human liver, which equates to an approximate 100‐fold higher level of expression. H6PDH mRNA was also detected with a mean ΔCT of 14·46 (range 13·13–16·60), approximately 35‐fold more abundant than 11β HSD‐1 in skeletal muscle. There was a significant correlation between 11β HSD‐1 and H6PDH (r = 0·67, P = 0·03). 11β HSD‐1 immunostaining was present in all muscle specimens, with similar distribution among fast and slow twitch fibres. 11β HSD‐1 oxoreductase activity was demonstrated, with mean conversion of cortisone to cortisol of 17·7% per 200 mg of muscle per 24 h (range 7·1–29·5%). Conclusions  11β HSD‐1 mRNA and protein is expressed in fresh human skeletal muscle along with readily demonstrable oxoreductase activity. 11β HSD‐1 localization is not muscle fibre type specific. High levels of skeletal muscle H6PDH should ensure that oxoreductase activity predominates in vivo.